Tensile properties and morphology of polyamide 6 (PA6)/ethylene vinyl acetate (EVA)/sepiolite nanocomposite - Fauzi, N. M. (2015)
This study was conducted in order to develop the new polymer nanocomposites. In this case, sepiolite was incorporated into Polyamide 6 (PA6) / Ethylene vinyl acetate (EVA) blend. The main aim of this research is to examine the effect of sepiolite concentration on the properties of PA6/EVA/sepiolite nanocomposite. The variations of sepiolite (2 – 10 phr) were added into PA6/EVA blend at the ratio of 80/20 wt%. The nanocomposites were prepared using twin screw extruder and injection moulding. Mechanical properties of PA6/EVA/sepiolite nanocomposite were analyzed by tensile testing and it was revealed that there is no change in stiffness and decrease in strength with more sepiolite content. Meanwhile, the morphology of materials was characterized by field emission scanning electron microscopy (FESEM). The morphology revealed that, the dispersion of sepiolite nanofiller seems to be good and the EVA domain size and distribution was effected by sepiolite content.